STRATEGI REKRUTMEN PEGAWAI UNTUK MEMBANGUN ORGANISASI YANG EFEKTIF - Achmad Purwono (Jurnal Manajemen Kepegawaian, 2009)
In this uncertainty situation, the activity of organization became more unstable. Recruitment strategy has astrategic role to prepare future and visionary organization to be an effective work place. To prepare the effectiveorganization a strategic recruitment created a strategic role as a beginning of future effective organizationthat can survive to deal with the dynamic of environment. According to create resilience of the organizationstrategic recruitment should be maintained with extra attention and using some alternative or option to makethis as a basic activity to achieve future organization.Key words: recruitment, strategy, effective organization.